1994
DOI: 10.1103/physrevlett.72.3843
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Induced Layer-by-Layer Growth of Ag on Ag(111): Origins and Side Effects

Abstract: It has been shown that submonolayer deposits of Sb change the growth mode of Ag(111) from multilayer to layer-by-layer.Using scanning tunneling microscopy, we identify the two main origins of this behavior. (i) Sb lowers the mobility of Ag adatoms on terraces and growing islands. As a direct consequence, the additional edge barrier (barrier to descend a step minus surface diffusion barrier) is reduced. (ii) Sb lowers the mobility along step edges, inducing dendritic island shapes. Both effects favor smoother g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
144
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(153 citation statements)
references
References 15 publications
9
144
0
Order By: Relevance
“…Additional step-edge growth simulations have shown that A edges grow considerably rougher than B edges, which further validates the effective implementation of the corner-crossing asymmetry in our KMC model [83]. Moreover, the smoothening of island B edges, leading to compact islands with increasing growth temperature, is consistent with Ag/Ag (111) homoepitaxial data [53,54] and shows that our model correctly treats adatom diffusion at the island periphery.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Additional step-edge growth simulations have shown that A edges grow considerably rougher than B edges, which further validates the effective implementation of the corner-crossing asymmetry in our KMC model [83]. Moreover, the smoothening of island B edges, leading to compact islands with increasing growth temperature, is consistent with Ag/Ag (111) homoepitaxial data [53,54] and shows that our model correctly treats adatom diffusion at the island periphery.…”
Section: Resultssupporting
confidence: 68%
“…A physical model based upon a bond-counting scheme is first developed using Ag/Ag(111) homoepitaxy as a starting point, chosen due to the immense experimental and theoretical literature on this film/substrate system [41,43,[53][54][55][56]. The model is validated by showing that simulations: (i) reproduce experimentally observed trends of island morphological evolution during Ag/Ag(111) homoepitaxy as a function of film-growth temperature [54], and (ii) yield equilibrium island shapes upon annealing, at elevated temperatures and in the absence of deposition, of hemispherical islands on weakly interacting substrates [57].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to Ag on Ag͑111͒ homoepitaxy, where limited interlayer transport caused by the step edge barrier results in 3D growth. 7,8 It was proposed that the large density of kink sites originating from the boundaries of stacking-fault islands could offer channels with reduced step edge barriers to promote interlayer diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reduction of the overall mobility had been observed experimentally, and deduced from ab initio calculations for Ag͑111͒ homoepitaxy in the presence of Sb surfactant atoms. [23][24][25] At the same time that Rh-Ag islands form, the substrate undergoes complementary morphological changes. Specifically, the steps roughen, starting at 0.02 ML, until by 0.30 ML, fjordlike vacancy structures extend from the step edges.…”
mentioning
confidence: 99%